The Particle Induced Mode Splitting and Exceptional Points in Whispering-Gallery Mode Microcavity - Jin Xiao-Xue; Yong-Pan Gao; Zheng Shi-Hui; Tie-Jun Wang; Chuan Wang (IEEE Photonics Journal)
The manipulation of optical modes is an important issue for the realization of sensors in microcavities. In this paper, the generation and modulation of mode splitting in optical microcavities is studied by controlling the axes of an ellipsoidal nanoparticle. Different from the previous schemes, mode splitting and mode broadening caused by ellipsoidal particle scattering are related to the axial orientation of the particle. Therefore, unlike the scheme in which the relative position of the bi-spherical particles must be adjusted to modulate the relative coupling phase, the coupling strength and dissipation of the mode could be tuned by controlling the axial orientation of the ellipsoidal particle in our scheme. Furthermore, it can also tune the system to the exceptional points. This provides a novel way to manipulate the exceptional points in the whispering-gallery mode microcavity.